167k views
2 votes
If f(x) = 2x + 4 and 9 (20) = x - 3, find f (g(x)).

If f(x) = 2x + 4 and 9 (20) = x - 3, find f (g(x)).-example-1
User Dan Lugg
by
5.0k points

1 Answer

2 votes

Answer: D

Explanation:

To find f(g(x)), you want to take g(x) and plug that into f(x). Since we are given f(x) and g(x), we can go ahead and do that.

f(g(x))=2(x-3)+4 [distribute]

f(g(x))=2x-6+4 [combine like terms]

f(g(x))=2x-2

Now, we know that f(g(x))=2x-2.

User Knightpfhor
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.